Perkawinan Kontrak Dalam Perspektif Hukum Keluarga Islam - Putra, Miryando Eka; Putra, Marwan Jaya; Ja'far, A. Kumedi (Laskar Karya, 2024)
This paper examines contract marriage from the perspective of Islamic family law. Contract marriage, or nikah mut'ah, is a form of temporary marriage recognized in the Shia tradition but rejected by the Sunni school. This practice is regulated by the determination of duration and conditions agreed upon by both parties, so it does not require an official divorce. This paper discusses the differences in views between the Shia and Sunni schools regarding nikah mut'ah, and its implications for women's rights and family integrity. From the Shia perspective, nikah mut'ah is seen as a legitimate legal solution, while the Sunni view it as a practice that is inconsistent with the purpose of marriage in Islam. In addition, this paper highlights the social impact of nikah mut'ah, especially in terms of protecting women's rights, and compares it with the practice of nikah misyar. This study uses a qualitative method with a normative approach, including analysis of Islamic legal literature, fiqh, and related regulations in various countries. The results show that although nikah mut'ah is recognized in some contexts, this practice often causes injustice to women and damages the family structure, thus requiring better regulation and legal protection.